Relation of blood lead levels and lead in gasoline: an updated systematic review - Ruth C. Angrand; Geoffrey Collins; Philip J. Landrigan; Valerie M. Thomas (BMC, 2022)
Abstract Background Millions of tons of lead were added to gasoline worldwide beginning in 1922, and leaded gasoline has been a major source of population lead exposure. In 1960s, lead began to be removed from automotive gasoline. Removal was completed in 2021. Objectives To determine whether removal of lead from automotive gasoline is associated with declines in population mean blood lead levels (BPb). Methods We examined published studies that reported population blood leaded levels for two or more years, and we calculated average concentrations of lead in gasoline corresponding to the years and locations of the blood lead level measurements. Results Removal of lead from gasoline is associated with declines in BPb in all countries examined. In some countries, BPb continues to fall after lead has been eliminated from gasoline. Following elimination of lead from gasoline, BPb less than 1 μg/dL have been observed in several European and North American countries, and BPb less than 3 μg/dL have been documented in several studies from South America. Discussion There remain many countries for which no multi-year studies of populations BPb have been identified, including all of Central America, high population countries including Pakistan and Indonesia, and major lead producers including Australia and Russia. Conclusion Removal of lead from gasoline has been a public health success. Elimination of lead from gasoline has enabled many countries to achieve population mean BPb levels of 1 μg/dL or lower. These actions have saved lives, increased children's intelligence and created great economic benefit in countries worldwide.